2020
DOI: 10.1029/2020je006701
|View full text |Cite
|
Sign up to set email alerts
|

Amorphization of S, Cl‐Salts Induced by Martian Dust Activities

Abstract: Amorphization of S and Cl salts was induced by electrostatic discharge (ESD) in a Mars chamber that simulates martian dust activities. • Amorphization is commonly accompanied by dehydration of salts and the oxidation of Fe, Cl, and S species. • Dust activities may have generated and deposited large quantities of Sand Cl-rich amorphous materials all over the martian surface.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 100 publications
(249 reference statements)
0
12
0
Order By: Relevance
“…Sulfates and chlorides are among the most common salts deposited both in the Qaidam Basin and on Mars. 53 The sulfate and chloride components sampled from the Qaidam Basin have been found to exist in a form with a high degree of hydration in spite of the arid conditions, and such hydrates have also been found on Mars. [36][37][38] An important type of Martian sulfates is in the form of Mg sulfates.…”
Section: Discussionmentioning
confidence: 99%
“…Sulfates and chlorides are among the most common salts deposited both in the Qaidam Basin and on Mars. 53 The sulfate and chloride components sampled from the Qaidam Basin have been found to exist in a form with a high degree of hydration in spite of the arid conditions, and such hydrates have also been found on Mars. [36][37][38] An important type of Martian sulfates is in the form of Mg sulfates.…”
Section: Discussionmentioning
confidence: 99%
“…The typical Raman and MIR peaks of Mg(ClO 3 ) 2 and MgCO 3 were not seen from the remaining salts of 7hr‐ESD‐on‐MgCl 2 , perhaps due to their presence as amorphous forms because MgCl 2 was observed to become amorphous after 7 hr‐ESD (A. Wang, Yan, Dyar, et al., 2020). XRD analyses of remaining salts of ESD‐on‐KCl and ESD‐on‐MgCl 2 showed no detection of chlorates or carbonates suggesting low concentrations (<1 mol%).…”
Section: Resultsmentioning
confidence: 99%
“…First, 0.0001 was used as the ESD occurrence probability during GDS (Table S5c in Supporting Information S1), which was arbitrarily selected in an early study (A. Wang, Yan, Dyar, et al, 2020), but was retained to keep the consistency throughout our studies. A probability of 1-2 orders of magnitude higher is entirely possible, pending the real measurement of electrical properties of dust activities on Mars in the future, like the payloads prepared by Farrell et al (2000) for NASA and Harrison et al (2016) for ESA missions.…”
Section: Scale To Mars From the Quantifications Of This Studymentioning
confidence: 99%
“…Wu et al [ 44 ] found that the oxidation power of ESD electron is three orders of magnitude higher than that of UVC photon. Besides, ESD processes are also responsible for the amorphization of S‐ and Cl‐bearing compounds, [ 47 ] which is commonly accompanied by the dehydration of these salts. Thus, it is proven that ESD activity is of great importance in the sulfur cycle, which has been observed in the studied meteorite, ClO 4 2− .…”
Section: Resultsmentioning
confidence: 99%